3D flexible displacement sensor for highly sensitive movement measurement assisted by the terahertz imaging system - Meng, Tianhua; Zhao, Guozhong; Liu, Hongmei; Li, Wenyu; Feng, Caixia; Hu, Weidong (Frontiers in Materials, 2022)
Aiming at the difficulty of accurately calibrating the sample position in the terahertz (THz) imaging process, especially in the defect imaging detection and the precise characterization of the edge profile, a flexible and highly sensitive 3D terahertz displacement sensor with a resolution of up to 1 μm was proposed by the artificial electromagnetic metamaterials. The high resolution of the flexible sensor can be attributed to the used artificial electromagnetic metamaterials with the enhancing sensitivity of THz sensors as well as the flexible substrate with the high fitting to the target. Different from the laser displacement sensor with a complex and large volume of the generating device, the proposed flexible sensor with a simple structural design is composed of only a fixed layer and a displacement indicating layer. The fixed layer is composed of the Mylar flexible substrate layer and the metal split resonator ring on it, and the displacement indicating layer is composed of the Mylar flexible substrate layer and the metal indicator lines on it. With using this unique double-layer structure, high-sensitivity measurement of displacement can be achieved by measuring the moving amount of the metal indicator line corresponding to the valley change in the THz transmission of the displacement sensor. The results demonstrate that the sensitivity of the displacement sensor can reach 145 GHz/μm, the quality factor Q can reach 194.67, and the quality factor figure of merit (FOM) can reach 6.25 μm-1. Compared with the mature commercial displacement sensors and laser displacement sensors, the proposed sensor can have the characteristics of compact structure, simple preparation process, high sensitivity, and flexibility, which can offer certain advantages for the realization of high precision, miniaturization, and distributed sensing systems in the future.